Economic Analysis of Tobacco and Options for Tobacco Control : China Case Study - Hu, Teh-Wei; Mao, Zhengzhong (World Bank, Washington, DC, 2013)
China has a very high prevalence rate of cigarette smoking. According to a 1996 Chinese national survey, 63% of adult males (age 15 and over) and 3.8% of adult females were current smokers (Chinese Academy of Preventive Medicine, 1997). These prevalence rates indicate that there are over 320 million cigarette smokers in China, which accounts for nearly one-third of the smokers in the world (Collishaw, 1998). Moreover, it has been estimated that there are 460 million second hand smokers in China (Zhu, 1996). In other words, more than two-thirds of the Chinese population in the country face health hazards that can be attributed to smoking. Given the size of its smoking population, China consumes more cigarettes than any other country in the world. It also produces more cigarettes than any other country. In 1997, China produced 33.67 million cases or 84.18 billion packs (one case consists of 2,500 packs) of cigarettes and used 1.31 million hectares for tobacco production (China Statistics Bureau, 1998). It is well known in developed countries that cigarette smoking has major hazardous health consequences. In past decades, many developed countries have adopted various tobacco control policies to reduce cigarette consumption. As a result, per capita cigarette consumption in developed countries has been declining. On the other hand, among developing countries such as China, the negative health consequences of smoking are less well known. For instance, in the 1996 Chinese national survey, 61% of those questioned responded that cigarette consumption posed no harm to their health (Chinese Academy of Preventive Medicine, 1997). Many government officials in the Ministry of Health and public health professionals in China have recognized the importance of tobacco control, and have made a substantial effort to discourage cigarette consumption through a public health campaign. However, they have been unable to convince the State Development and Planning Commission and the Ministries of Finance, Economics and Trade and Agriculture to support tax increases as a means to control tobacco.